Tingkat Kepuasan Mahasiswa pada Proses Belajar Mengajar Jarak Jauh - Suliyanthini, Dewi; Irwan, Annisa Zahra; Lubis, Harsuyanti; Radiona, Vivi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The pandemic that has hit the whole world requires the teaching and learning process to be carried out online or distance learning, by utilizing information technology, electronic media as a medium for delivering learning materials during a pandemic and during social restrictions. Descriptive Quantitative Research Methodology by conducting a survey to students of the Fashion Design Education Study program, Faculty of Engineering – State University of Jakarta, Class of 2017 to Class of 2021, with a population of 289 students, calculations using the Slovin sample formula resulted in a sample of 145 students. The results of the study, resulted in the level of student satisfaction in the online distance learning process which includes Empathy: 28%, responsiveness 32%, certainty 21%, reliability 19%. This shows that the delivery of lecture material online is less than optimal